Associations between radiographic features, clinical features and ultrasound of thumb‐base osteoarthritis: A secondary analysis of the COMBO study. (24th November 2021) - Shi, Ying; Fu, Kai; Oo, Win Min; Deveza, Leticia A.; Wang, Xia; Duong, Vicky; Robbins, Sarah R.; Hunter, David J.
Abstract: Aim: To investigate the associations of ultrasound and radiographic features of thumb‐base osteoarthritis (OA) with thumb‐base pain and hand function at baseline and 12 weeks. Method: Data from a randomized controlled trial conducted in participants with symptomatic radiographic thumb‐base OA were analyzed. Participants who finished follow up were included in this secondary analysis. Pain and hand function were assessed using self‐reported measures. All participants underwent ultrasound examinations for synovitis, power Doppler signal (PDS), and osteophytes, and underwent radiography for osteophytes, joint space narrowing (JSN), and subchondral bone sclerosis at baseline. Hand pain and function were reassessed after the 12‐week follow up. The associations of ultrasound and radiographic findings with clinical features were further evaluated, using linear regression analyses, after adjustment for relevant confounding factors. Results: A total of 166 participants (average age 66.2 years; 76.5% female) were included. At baseline, radiographic JSN and subchondral bone sclerosis were associated with hand function. There was a significant association between ultrasound‐detected PDS and patient's global assessment (PGA) at baseline. Baseline radiographic JSN was significantly associated with the changes in stiffness and PGA from baseline to 12 weeks. There was no association between ultrasound features and changes in the clinical outcomes over 12 weeks. Conclusion: This study indicates that radiographic features significantly correlate with hand function, and ultrasound PDS is closely related to the PGA at baseline in thumb‐base OA. Radiographic JSN may be a predictor for stiffness and PGA in thumb‐base OA.